Physical Education in school health plans from Brazil and Spain (Agora for Physical Education and Sport, 2020)
This article aims to analyze the role of Physical Education within the scope of School Health Plans in Brazil and Spain, based on the principles of the Schools for Health Network in Europe and Latin America. It is a study with a qualitative approach, descriptive-analytical nature and critical perspective. The principles established in the theoretical framework of both plans are relevant, but point out some contradictions in the physical education approach. In addition, the failures in its implementation process did not allow the structural changes necessary to strengthen Health Education in schools.
Keywords: school health; physical education; health education; health promotion